Can the Assembly of First Nations Education Action Plan Succeed? Colonialism’s Effect on Traditional Knowledge in Two Communities. - Spence, Martha E.
have altered the context and practices of the First Nations culture and by so doing, compromised their will and capacity to implement traditional education policies, a situation that must be linked to realization of the Education Action Plan’s goals. The goal of the study was to assist policy makers, community leaders, and educators in recognizing the attitudes, social norms, and practices that are interwoven with post-colonial trust issues at the community level and to focus on the viability of preservation of First Nations heritage and culture. The inquiry documented and analyzed, in a case study approach, the dynamics of colonialism on two First Nations communities. Interviews and questionnaires, utilized in communities, were based on a matrix that directed comments to areas associated with traditional knowledge, remnants of colonialism and areas of will and capacity. The focus of the inquires referred to curriculum content, funding, school and community structure, as well as traditional knowledge, communication, participation, and the role of members in shaping the community values and school curricula. In all, 32 people were formally interviewed including teachers, Elders, education council members, principals, and community leaders. The study comprised 14 interviews and 17 questionnaires in Two Rivers, and 18 interviews and 8 questionnaires in Round Rock. The study intended to establish whether colonialism would play out in the implementation of the traditional knowledge aspect of the Education Action Plan and if so, in what areas and in what manner. Through research, it was EDD